Penanganan Virus pada Buah Naga dan Desain Atap Otomatis Kebun Buah Naga di Jl. Soekarno Hatta KM 25 Balikpapan - Andre Amba Matarru; Faisal Manta; Hadhimas Dwi Haryono; Bintara Alfaris; Muhammad Iskandar; Ferly Ardian Nur; Annisa Nurlaili; Fariidah Rahmah Deviyani; Kan Grizzel A. F. Kamagi; Inayah An Nabila; Santy Sarah Zhafirah (Abdimas Universal, 2023)
Dragon fruit is one type of fruit that can grow in tropical and subtropical areas such as Indonesia. Especially East Kalimantan Province, dragon fruit cultivation one of the people's livelihoods. In Karang Joang Village, KM 25 Balikpapan, there are dragon fruit farmers who experience problems related to dragon fruit plants growing in their gardens. Dragon fruit plants in the garden were attacked by diseases caused by viruses due to frequent exposure to rain. Handling the virus with herbal medicines that are easily available, making it easier for the operational costs of dragon fruit planting to be affordable. Spraying of herbal medicine is carried out on dragon fruit about 3 times a week with a garden area of 3-4 hectares. In addition, innovation is also given in making prototypes of automatic roofs in order to protect plants from extreme weather that can affect soil and plant conditions. Through the manufacture of this automatic roof prototype, it is hoped that it can help protect dragon fruit trees when they are in a season with high rainfall.